MacIntyre, rival traditions and education. Issue 3 (3rd May 2016) - Stolz, Steven A.
Abstract : This paper critically discusses MacIntyre's thesis that education is essentially a contested concept. In order to contextualise my discussion, I discuss both whether rival educational traditions of education found in MacIntyre's work – which I refer to as instrumental and non-instrumental justifications of education – can be rationally resolved using MacIntyre's framework, and whether a shared meaning of education is possible as a result. I conclude that MacIntyre's synthesis account is problematic because the whole notion that there are rationally negotiable ways in which to compromise or harmonise opposing justifications of education found in instrumental and non-instrumental forms of education is troubling – the reason being that these are cultural disagreements about human flourishing that are not neutral-free, and due to a lack of care distinguishing between the common uses of the term 'education', and its looser usages to mean something like school learning that embraces a range of aims and goals that are often incompatible. In this light, it is argued that the contestability card has been unnecessarily overemphasised, and brings to our attention the complex ways in which we interpret education and what it means to be educated.